The Activity of Alkanna Species in vitro Culture and Intact Plant Extracts Against Antibiotic Resistant Bacteria - Sahakyan, Naira; Petrosyan, Margarit; Trchounian, Armen (Current Pharmaceutical Design, 2019)
Overcoming the antibiotic resistance is nowadays a challenge. There is still no clear strategy to combat this problem. Therefore, the urgent need to find new sources of antibacterial agents exists. According to some literature, substances of plant origin are able to overcome bacterial resistance against antibiotics. Alkanna species plants are among the valuable producers of these metabolites. But there is a problem of obtaining the standardized product. So, this review is focused on the discussion of the possibilities of biotechnological production of antimicrobial agents from Alkanna genus species against some microorganisms including antibiotic resistant bacterial strains.
Keywords: Bacterial resistance